Suppressing Electromagnetic Interference in Switching-Mode Power Supplies by Chaotic Carrier Frequency Modulation: - Niu, Junying, (VDI Verlag, 2017)
Due to the unpredictable and random-like features of chaotic signals, chaotic carrier frequency modulation (CCFM) technique, by which the spectra of input and output signals can be spread over a wide frequency band without changing the total energy, has been used to suppress electromagnetic interference (EMI) of switching mode power supply (SMPS). So far, the study on CCFM was focused on theoretical analyses, simulations, and experimental verifications, lacking of a practical consideration of applying CCFM in real power supplies, which will be main concern of this dissertation. To provide efficient and economical EMI suppression solutions, a CCFM module is proposed to serve as a plug-in component for power supplies with standard PWM ICs, and for designing a chaotic frequency PWM IC, it is necessary to integrate a chaotic frequency oscillator into the standard PWM IC, which is to be realized both in analogue and digital manners for various practical applications....